Content-Based Instruction: The Significance of Teaching Graphic Novels in the Development of Productive Language Skills of EFL Learners - Hama, Asst. Prof. Dr. Bakhtiar Sabir; Student), Dalya Abdalstar Faqe Othman (MA (Sulaimani Journal for Humanities, 2023)
The present study examines the impact of graphic novels on the development of productive language skills among English as a Foreign Language (EFL) learners in private schools located in Sulaimani City, Kurdistan Region. The study aims at drawing the attention of EFL learners and teachers and at the same time the researchers to the significance of graphic novels in language learning and how they can be used as effective teaching tools to achieve this purpose. Additionally, the study intends to illustrate how graphic novels can facilitate the improvement of productive language skills, specifically speaking and writing, among EFL learners. To prove this methodically, the researcher collected data from two private schools since pupils in such schools are more aware of graphic novels and they read and study it. The study employs a mixed-methods approach to gather and analyze data on the ways that EFL learners respond to graphic novels as a tool for language learning. The researcher used a questionnaire to collect and analyze data from 150 students at Kurd Genius School (Secondary and Primary School) and Cambridge International School during the academic year 2021-2022. The data of this study was analyzed using the IBM SPSS program. The findings proved that teaching graphic novels is effective in developing productive language skills, namely speaking and writing, for learners of English as a foreign language, and they also provide teachers and decision makers with convincing justifications to incorporate this tool into the school curricula to improve and accelerate the process of language learning among the EFL learners.
Keywords: productive skills; Graphic novels; Motivation; and Multimodality